On the Causal Relationship between Household Consumption and Economic Growth in Saudi Arabia - Al Rasasi, Moayad; Alzahrani, Yasir; Alassaf, Mohammed (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This research paper explores the causal relationship between household consumption and economic growth over the period of 1980-2017. Hence, it applies the popular cointegration tests alongside the most common causality test. The empirical analysis shows the presence of a positive long run relationship between household consumption and economic growth. In specific, we find evidence revealing that a one percent increase in household expenditures on consumption would boost economic growth by 0.7 percent. Furthermore, causality analysis, based on Granger (1969) test, suggests that variation in household consumptions could explain changes in economic growth.